Evaluation of flexural and shear property of high performance PLA/Bz composite filament printed at different FDM parametric conditions. (9th February 2022) - Sneha, P.; Balamurugan, K.; Kalusuraman, G.
In the present work, 14% bronze (Bz) with a particle size of 10-20 μm is used as reinforcement in the PLA matrix to obtain a composite 3D filament. The bonding properties of Bz particles in the PLA matrix are uniform and excellent. The manufactured composite filament is printed under different parameters of the fused deposit model at a matrix angle of 45°. The density, bending and shear properties of the printed specimens were evaluated according to ASTM standards. The nozzle temperature, bed temperature and Layer height were taken as independent parameters. The layer height had an impact on other output parameters. Fracture mechanics are analysed through scanning electron microscopy and 3D optical microscopy. The bending and shearing test specimens present a plastic deformation failure. The push mechanism of the particles has been observed, and most of the fracture surface is subject to wear caused by the Bz particles.